Spatial structure of shell polychromatism in Cepaea hortensis in relation to a gradient of landscape fragmentation in Western France - Le Mitouard, Eric; Bellido, Alain; Guiller, Annie; Madec, Luc (Landscape ecology, 2010)
Because of their highly polymorphic shell patterns, Cepaea land snails have been the subject of numerous studies in ecological genetics. Here, we investigated the spatial structure of polychromatism in Cepaea hortensis in agricultural landscapes with zones from low to high hedgerow densities. Our main purpose was to search for a relationship between landscape composition and spatial structuring of chromatism. Despite significant spatial heterogeneity in the three landscapes sampled, only the high hedgerow density landscape showed a significant spatial structuring of shell polymorphism. In order to understand this result, an investigation of daily movement patterns in relation to habitat form was carried out on a mark-release experiment under semi-artificial conditions. This experiment revealed a strong influence of a linear corridor on snail dispersal. In the field, spatial heterogeneity of shell polymorphism, related to the effects of genetic drift, was shaped by restricted dispersal in narrow corridors. In the more enclosed one, i.e. where hedgerow density was the highest, the significant spatial structure we detected involved a balance between local genetic drift and environmentally mediated gene flow. This isolation-by-distance pattern resulted from direct gene exchange through fields between neighbouring populations. When applying landscape distances based on hedgerow length, no significant spatial correlation with polychromatism was found. In the more fragmented sites, random genetic drift seemed to be the prevailing force and, at the scale of the whole sampled area, selective pressures potentially interfere with these genetic drift-dispersal events.